2020
DOI: 10.1101/2020.06.18.158584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unexpected free fatty acid binding pocket in the cryo-EM structure of SARS-CoV-2 spike protein

Abstract: COVID-19, caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), represents a global crisis. Key to SARS-CoV-2 therapeutic development is unraveling the mechanisms driving high infectivity, broad tissue tropism and severe pathology. Our cryo-EM structure of SARS-CoV-2 spike (S) glycoprotein reveals that the receptor binding domains 5 (RBDs) tightly and specifically bind the essential free fatty acid (FFA) linoleic acid (LA) in three composite binding pockets. The pocket also appears to be pres… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…3D). We did not observe any additional density that would correspond to bound lipids such as those described in a recent preprint (19), or other bound co-factors. These may be present sub-stoichiometrically or in rare conformations but are not a general feature of the S trimer in situ.…”
Section: Virions In the Supernatant Of Infected Cells Show Primarily contrasting
confidence: 50%
See 2 more Smart Citations
“…3D). We did not observe any additional density that would correspond to bound lipids such as those described in a recent preprint (19), or other bound co-factors. These may be present sub-stoichiometrically or in rare conformations but are not a general feature of the S trimer in situ.…”
Section: Virions In the Supernatant Of Infected Cells Show Primarily contrasting
confidence: 50%
“…The prefusion structure of S from coronaviruses including SARS-CoV-2 has been extensively studied using ectopic expression of a soluble, secreted form of S, followed by purification combined with cryo-EM and single particle reconstruction (7,8,(18)(19)(20). In the prefusion form, the receptor binding domain (RBD) sits at the top of a broad, trimeric spike, above the fusion core.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linoleic acid, an essential free fatty acid, was buried within a hydrophobic pocket in the CTD with its main chain carboxyl group making contacts with the adjacent RBD in closed conformation. A recent report by Toelzer et al also identified this density and attributed it to the presence of linoleic acid (34). The second large density occupied by PS 80 is situated in the NTD and is relatively more surface exposed.…”
Section: Glycan Occupancy and Glycan Processingmentioning
confidence: 79%
“…state (34). Recent reports by Henderson et al have revealed that mutations at certain positions can alter the propensity toward 'up' and 'down' states of the RBD (36,37).…”
Section: Glycan Occupancy and Glycan Processingmentioning
confidence: 99%